Clinical and radiological long-term results after operative treatment of chondroblastoma - Lehner, Burkhard; Witte, Daniela; Weiss, Stefan (Archives of orthopaedic and trauma surgery, 2011)
Introduction The aim of this study was the investigation of radiological and clinical long-term results after surgery for chondroblastoma in a single orthopedic oncological center. Method As much as 24 patients were enrolled in the study using an in-house tumor data-base (age, sex, patient history, clinical symptoms, type of surgery, complications, and histological results), radiological findings (localization/size of the lesion, Lodwick-classification, Enneking-stages, and local recurrence), and clinical investigation (Enneking score). Mean follow-up was 8 years. Results Preferred sites were the knee-joint (distal femur 6, proximal tibia 6), followed by the proximal humerus (8), and the proximal femur. As much as 3 lesions were judged inactive, 13 active, and 8 aggressive. Apart from one case, all lesions were treated by curettage and filling of the defect by bone cement and/or cancellous bone chips. Only one patient suffered local recurrence after primary resection of the tumor (4.2%). About 87.5% of our patients reached a very good or good functional result (Enneking score 28-30). Conclusion Our results further support curettage and defect filling even of active/aggressive chondroblastoma. If performed betimes, the surgical therapeutic concept of accurate intralesional curettage with or without local adjuvant therapy and defect packing with cancellous bone grafts and/or bone cement assures a high chance of joint preservation along with a low rate of recurrence and good functional long-term results.